2019
DOI: 10.1002/ps.5404
|View full text |Cite
|
Sign up to set email alerts
|

Endothall behavior in Myriophyllum spicatum and Hydrilla verticillata

Abstract: BACKGROUND: Endothall has been used to control submersed aquatic plants since 1960, providing broad-spectrum control of aquatic weeds. Although endothall is considered a contact herbicide, many field observations suggest that it might have systemic activity. The goals of this research were to determine endothall's (i) absorption characteristics, (ii) translocation from shoots to roots, and (iii) potential for desorption in Eurasian watermilfoil (EWM), monoecious and dioecious hydrilla. RESULTS: Endothall absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…After only 1 h 2,4‐D BEE PCF was 16.78 ± 0.32, 30 times greater than 2,4‐D's PCF at the same time (0.53 ± 0.01). Even though 2,4‐D and 2,4‐D BEE bioaccumulation was greater in HWM than in EWM, increased herbicide accumulation does not necessarily equate to better control 25 and therefore, herbicide absorption does not contribute to 2,4‐D resistance in HWM. One possible explanation for greater herbicide accumulation in HWM could be due to its faster growth rate and lower herbicidal impacts on plant growth.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…After only 1 h 2,4‐D BEE PCF was 16.78 ± 0.32, 30 times greater than 2,4‐D's PCF at the same time (0.53 ± 0.01). Even though 2,4‐D and 2,4‐D BEE bioaccumulation was greater in HWM than in EWM, increased herbicide accumulation does not necessarily equate to better control 25 and therefore, herbicide absorption does not contribute to 2,4‐D resistance in HWM. One possible explanation for greater herbicide accumulation in HWM could be due to its faster growth rate and lower herbicidal impacts on plant growth.…”
Section: Resultsmentioning
confidence: 94%
“…31 Another study looking at aquatic herbicide desorption demonstrated that although endothall's log K ow is −0.55, it binds irreversibly to several serine/threonine protein phosphatases; therefore, endothall's desorption in EWM by 96 HAT was only 28.92% ± 15.63% well below equilibrium with the water column. 25 Even though HWM desorption was slightly lower than EWM, 2,4-D and 2,4-D BEE desorption in both plant species is driven mainly by a concentration gradient, and the establishment of a dynamic equilibrium between the shoots and water column; therefore, herbicide desorption does not appear to play a role in 2,4-D resistance in HWM.…”
Section: Herbicide Desorptionmentioning
confidence: 89%
See 2 more Smart Citations
“…Inhibitors, such as cantharidin and endothall, bind to a hydrophobic pocket of the PP active site. Endothall is a very effective herbicide to manage weeds in aquatic environments [34].…”
Section: Novel Mechanisms Of Actionmentioning
confidence: 99%